2018
DOI: 10.3233/jad-180768
|View full text |Cite
|
Sign up to set email alerts
|

Midlife Physical Activity, Psychological Distress, and Dementia Risk: The HUNT Study

Abstract: Background: Physical activity (PA) is associated with a decreased dementia risk, whereas psychological distress (distress) is linked to an increased dementia risk.Objective: We investigated independent and joint associations of midlife moderate-to-vigorous PA (MVPA) and distress with incident dementia.Methods: Our study comprised 28,916 participants aged 30-60 years from the Nord-Trøndelag Health Study (HUNT1, 1984(HUNT1, -1986. Data on MVPA and distress from HUNT1 was linked to the Health and Memory Study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 43 publications
3
37
1
2
Order By: Relevance
“…At least weekly midlife moderate-to-vigorous physical activity (breaking into a sweat) was associated with reduced dementia risk over a 25-year period of follow-up (HR 0·8, 95% CI 0·6–1·1) but the confidence intervals were wide. 89 In contrast the Whitehall Study reporting on the 28-year follow-up of 10 308 people, found that more than 2·5 hours of self-reported moderate-to-vigorous physical activity per week, lowered dementia risk over 10, but not 28 years. 33 Very long-term studies are unusual; however, one 44-year study recruited 191 women (mean age 50) purposively to be representative of the Swedish population and reported that 32% of the participants with low baseline peak fitness, 25% with medium, and 5% with high fitness developed dementia (high vs medium HR 0·1, 95% CI 0·03–0·5, low vs medium 1·4, 0·7–2·8).…”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 95%
See 1 more Smart Citation
“…At least weekly midlife moderate-to-vigorous physical activity (breaking into a sweat) was associated with reduced dementia risk over a 25-year period of follow-up (HR 0·8, 95% CI 0·6–1·1) but the confidence intervals were wide. 89 In contrast the Whitehall Study reporting on the 28-year follow-up of 10 308 people, found that more than 2·5 hours of self-reported moderate-to-vigorous physical activity per week, lowered dementia risk over 10, but not 28 years. 33 Very long-term studies are unusual; however, one 44-year study recruited 191 women (mean age 50) purposively to be representative of the Swedish population and reported that 32% of the participants with low baseline peak fitness, 25% with medium, and 5% with high fitness developed dementia (high vs medium HR 0·1, 95% CI 0·03–0·5, low vs medium 1·4, 0·7–2·8).…”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 95%
“…The Norwegian HUNT study, suggested that symptoms of psychological distress predicted dementia 25 years later however with wide bounds of uncertainty (HR 1·3, 95% CI 1·0–1·7). 89 Two further studies differentiate between late-life and earlier life depressive symptoms. The UK Whitehall study, in a follow-up of 10 189 people, reports that in late life these symptoms increase dementia risk but not at younger ages (follow-up 11 years HR 1·7; 95% CI 1·2–2·4; follow-up 22 years 1·0, 0·7–1·4).…”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…Such benefits are believed to reduce neuropathological damage and increase or maintain cognitive reserve [ 67 ]. Evidence in the literature of the effects of exercise on lowering the risk of dementia shows favorable results in longitudinal observational studies of over 20 years of follow up [ 68 , 69 , 70 , 71 ]. Nevertheless, a recent systematic literature review on physical activity interventions for slowing and delaying cognitive decline, cognitive impairment and dementia in individuals without diagnosed cognitive impairments found insufficient evidence for such claims [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, and in particular studies on mice models (Intlekofer and Cotman, 2013), physical exercise has been thought of as neuroprotective for neurodegenerative pathologies (Paillard et al, 2015). PA could thus influence age-related decline (Hamer et al, 2018;Lerche et al, 2018;Loprinzi et al, 2018;Engeroff et al, 2019) -particularly on episodic memory (Hamer et al, 2018) -and would be related to a lower risk of later onset of dementia (Guure et al, 2017;Zotcheva et al, 2018). As for the underlying mechanisms, two modes of action are reported.…”
Section: Activitiesmentioning
confidence: 99%